Clinical and Functional Outcomes of Arthroscopic Bankart Repair among Patients with Recurrent Anterior Shoulder Dislocation - Naveed Ali Shair; Muhammad Abubakar; Rehan Sittar; Syed, Muhammad Khalid; Abdullah Tariq; Muhammad Hanif Mian (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To note the functional outcome of recurrent anterior shoulder dislocation with Bankart repair (BR) treated with arthroscopic stabilisation with suture anchors. METHODOLOGY: This prospective cohort study was conducted at the Department of Orthopedic Surgery, Lahore General Hospital, Lahore, from January 2021 to June 2022. Patients undergoing arthroscopic BR with anterior instability of the glenohumeral joint with at least >6 episodes of dislocation/subluxation in the last six months were analysed. Functional outcomes were assessed at one-month, three-month and six month intervals post-surgery using "Modified University of California Los Angeles (UCLA)" and "Simple Shoulder Test (SST)". RESULTS: Of 25 patients, 24 (96.0%) were male. The mean age was 27.20±4.0 years. The mean duration of symptoms was 9.1±6.2 months. In 16 (64.0%) patients, 2-suture anchors were utilised, while 3-suture anchors were used in the remaining 9 (36.0%) patients. Pre-surgery, the mean UCLA score was 16.4±5.6 and improved to 1-month, 3-month and 6-month as 16.6±5.1, 22.8±6.2 and 28.4±6.6 respectively (p<0.001). Pre-surgery, the mean SST score was 4.7±2.4 which improved to 1-month, 3-month and 6-month as 5.4±2.6, 8.1±3.3 and 11.2±3.1 respectively (p<0.001). All patients (100%) had full range of motion after six months post-surgery. CONCLUSION: Arthroscopic BR in recurrent anterior shoulder dislocation was a reliable procedure regarding functional outcomes and range of motion after six months of follow-up.